2008
DOI: 10.1097/mph.0b013e318165b2cc
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Acupuncture in Children

Abstract: Acupuncture has been used therapeutically in China for thousands of years and is growing in prominence in Europe and the United States. In a recent review of complementary and alternative medicine use in the US population, an estimated 2.1 million people or 1.1% of the population sought acupuncture care during the past 12 months. Four percent of the US population used acupuncture at any time in their lives. We reviewed 31 different published journal articles, including 23 randomized controlled clinical trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
136
0
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(155 citation statements)
references
References 50 publications
6
136
0
11
Order By: Relevance
“…Commonly, adverse events in children are redness and numbness at the acupuncture site, light-headedness and needle pain. 20 Anaesthesia precluded the children from experiencing needle pain and the sensation of lightheadedness. This study shows an incidence of POV rate, nearly twice the estimated incidence in the previous investigation in our department (Ariansen, unpublished observations, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, adverse events in children are redness and numbness at the acupuncture site, light-headedness and needle pain. 20 Anaesthesia precluded the children from experiencing needle pain and the sensation of lightheadedness. This study shows an incidence of POV rate, nearly twice the estimated incidence in the previous investigation in our department (Ariansen, unpublished observations, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It is significant, however, that although acupuncture on children has been shown to be feasible and acceptable, 50,[52][53][54] and children have shown little discomfort or fear, only 5 recent studies on the effectiveness of acupuncturepoint stimulation for CINV have included pediatric subjects. 45,[55][56][57] Cohen 58 has suggested that, to provide the best possible care, the physician balance 7 important factors when deciding whether to recommend a CAM treatment: (1) severity and acuteness of the illness; (2) curability with conventional treatment; (3) invasiveness, toxicities, and adverse effects of conventional treatment; (4) quality and evidence of safety and efficacy of the CAM treatment; (5) degree of understanding of the risks and benefits of conventional and CAM treatments; (6) knowledge and voluntary acceptance of those risks by the patient; and (7) persistence of the patient's intention to use CAM.…”
Section: Clinical Responsementioning
confidence: 99%
“…In a review, acupuncture was considered a safe modality for paediatric patients, but the authors advised that fewer needles should be used when treating children. 28 In accordance with this our study used one single point with light stimulation. As different acupuncture points result in different effects 29-32 55 the option of choosing points individually after analysing all symptoms presented in an ordinary clinical setting may increase effi cacy of future acupuncture treatment of colic.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%